BIAS AND IDEOLOGY IN WESTERN AND MIDDLE EASTERN MEDIA COVERAGE OF THE IRAN–ISRAEL WAR: A QUALITATIVE FRAMING ANALYSIS (Qualitative Research Journal for Social Studies, 2026)
The paper looks at how the media of the West and the Middle East framed the Iran war with Israel in various ideologies. The study employs the qualitative framing analysis with the assistance of critical discourse analysis to discuss the manner in which the news narratives created aggression, self-defense, retaliation, legitimacy, suffering in the civilian population and order in the region. This paper claims that strategic stability, deterrence, and security-focused explanations are generally favored in Western coverage and foregrounding of sovereignty, historical grievance, asymmetry, and humanitarian impact are more common in Middle Eastern coverage. Since peer-reviewed studies are yet to particularly examine the Iran-Israel war, the paper also utilizes relatively related studies on Israel-Palestine and Gaza coverage to interpret more generalized trends in the way the equivalent media systems frame conflict. The paper is placed against the backdrop of the April 2024 escalation following the attack on the Iranian consular office in Damascus and the June 2025 Israel-Iran conflict as outlined by the UK House of Commons Library that has seen Israel launch major strikes against Iranian nuclear and military targets and Iranian retaliatory strikes. Altogether, the paper demonstrates that media do not merely report on war but do construct the sense of the populace to choose, highlight, and to morally patternize the events into conflicting interpretations of legitimacy and blame.